Reliabilitas Tes Objektif Dalam Butir Soal Mata Pelajaran Bahasa Arab Assesment Akhir Semester SD Plus Intan Al-Sali Bandung - Cahyani, Esa; Fauzia, Eva Lathifah (Halaqa: Journal of Islamic Education, 2025)
Before the evaluation process, it is very important to measure the quality of a question. When a question is reliable, it can be said that the question has achieved its learning objectives. Test reliability is important in schools to ensure test quality, accurately measure student abilities, identify weaknesses, improve learning effectiveness, and increase trust. This study aims to determine whether the questions given to students are reliable or not so that students, parents, and the relevant school institutions can obtain test results that can be proven by the consistency of reliability assessment results. This study uses a quasi-experimental method with a multiple-choice Arabic language learning test instrument. The research population consists of 36 fourth-grade students, and 15 students were selected as samples. The data analysis technique is the Spearman-Brown product-moment formula. The hypothesis testing results were obtained at α 5%, with an rtable of 0.70 and a rhitung value of 1.998. The testing criteria state that if rhitung is greater than rtable, then H0 is accepted, confirming that there is a reliability coefficient for the objective test in the Arabic language subject for fourth-grade students at SD Plus Intan Al-Sali.